MALUF, Sônia Weidner; TORNQUIST, Carmen Susana (orgs.). Gênero, saúde e aflição: abordagens antropológicas, Florianópolis/SC, Letras Contemporâneas, 2010, 468 pp. - Marini, Marisol (Revista de Antropologia, 2012)
MALUF, Sônia Weidner; TORNQUIST, Carmen Susana (orgs.). Gênero, saúde e aflição: abordagens antropológicas, Florianópolis/SC, Letras Contemporâneas, 2010, 468 pp.